Tumor microenvironment and exosomes in brain metastasis: Molecular mechanisms and clinical application - Aili, Yirizhati; Maimaitiming, Nuersimanguli; Qin, Hu; Ji, Wenyu; Fan, Guofeng; Wang, Zengliang; Wang, Yongxin (Frontiers in Oncology, 2022)
Abstract：Metastasis is one of the important biological features of malignant tumors and one of the main factors responsible for poor prognosis. Although the widespread application of newer clinical technologies and their continuous development have significantly improved survival in patients with brain metastases, there is no uniform standard of care. More effective therapeutic measures are therefore needed to improve prognosis. Understanding the mechanisms of tumor cell colonization, growth, and invasion in the central nervous system is of particular importance for the prevention and treatment of brain metastases. This process can be plausibly explained by the “seed and soil” hypothesis, which essentially states that tumor cells can interact with various components of the central nervous system microenvironment to produce adaptive changes; it is this interaction that determines the development of brain metastases. As a novel form of intercellular communication, exosomes play a key role in the brain metastasis microenvironment and carry various bioactive molecules that regulate receptor cell activity. In this paper, we review the roles and prospects of brain metastatic tumor cells, the brain metastatic tumor microenvironment, and exosomes in the development and clinical management of brain metastases.